REINTERPRETASI AYAT GENDER DALAM MEMAHAMI RELASI LAKI-LAKI DAN PEREMPUAN (Kajian Kontekstual QS An-Nisa` ayat 34) - mayola andika (Jurnal Harkat : Media Komunikasi Gender, 2018)
Abstract. Nowadays, the issues of gender become hot topics to be discussed. It caused by the reality of some society who still hold the principle of patriarchal culture. Men tend to get the privileges than women. Basically, Islam upholds equality between men and women. Islam is believed as an ideal religion that is revealed for lift level and free up women from Jahiliyyah tradition in which marginalize women’s position. Verses of the Qur'an have revealed the equality of man and women and outline the equation in between both of them. As for the difference is their level of devotion. However, in religious empirical reality, the problem of gender bias arises whilst understanding and interpreting the religion texts. The misinterpretation then brought up the problem interrelated with men and women relation, for instance injustice, subordination, discrimination, and marginalization. Thus, the author assumes that a review of the interpretations of the verses and models of interpretation that tend to marginalize the role of women is needed to be conducted. In this research, the author elaborates of how the relation betwen men and women in Al-quran’s perspective through reinterpretation of Surat An-Nisa, verse 34 in contextual. The author focuses on the gender studies and connect it with the concept of men and women equality with descriptive-analitics method. Abstrak. Dewasa ini isu gender hangat diperbincangkan. Hal itu dilatarbelakangi oleh realitas masyarakat yang sebagian masih memegang prinsip budaya patriaki. Laki-laki mendapatkan hak-hak istimewa, sedangkan kaum perempuan cenderung dinomorduakan. Islam pada dasarnya menjunjung tinggi kesetaraan. Agama Islam diyakini sebagai agama yang ideal. Diturunkan untuk mengangkat derajat dan membebaskan perempuan dari tradisi jahiliyyah yang memarginalisasi kedudukannya. Ayat al-Qur’an telah mengungkapkan kesetaraan laki-laki dan perempuan serta menggariskan persamaan kedudukan di antara keduanya. Adapun yang membedakan adalah tingkat ketaqwaan. Namun, dalam realitas empiris keagamaan timbul problem pemahaman dan penafsiran teks-teks agama yang bias gender. Hal tersebut kemudian memunculkan masalah berkaitan dengan relasi laki-laki dan perempuan, seperti ketidakadilan, subordinasi, diskriminasi, dan marginalisasi. Untuk itu penulis menganggap perlu adanya peninjauan ulang interpretasi ayat dan model penafsiran yang cenderung meminggirkan peranan kaum perempuan. Dalam penelitian ini penulis memaparkan bagaimana relasi laki-laki dan perempuan dalam perspektif al-Qur’an melalui reinterpretasi terhadap penafsiran QS an-Nisa` ayat 34 secara kontekstual. Penulis memfokuskan kajian gender dan menghubungkannya dengan konsep kesetaraan laki-laki dan perempuan dengan metode deskriptif-analitis.